2022
DOI: 10.3389/fpls.2022.969718
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and physiological responses of different peony cultivars to high temperature

Abstract: In order to investigate the causes of the differences in heat tolerance (‘Lu He Hong’ and ‘Zhi Hong’), we studied the physiological changes, photosynthetic properties and regulatory mechanism of the two peony cultivars at high temperature. The results showed that the physiological changed of different peony cultivars varied significantly under high temperature stress. With the extension of high temperature stress time, MDA content of 'Lu He Hong' increased,while 'Zhi Hong' rised first and then decreased, SOD a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Tree peony (Paeonia suffruticosa Andrews), renowned as one of the top ten famous flowers in China, holds significant importance as a horticultural plant due to its ornamental, nutritional, and medicinal values [12,13]. Previous studies showed that the growth and development process of tree peony is regulated by some internal and external factors [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tree peony (Paeonia suffruticosa Andrews), renowned as one of the top ten famous flowers in China, holds significant importance as a horticultural plant due to its ornamental, nutritional, and medicinal values [12,13]. Previous studies showed that the growth and development process of tree peony is regulated by some internal and external factors [14].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, during the growth and development of tree peony, high temperatures and heat injuries are also significant obstacles [19]. They can disrupt the photosynthetic mechanism and influence the function of PSII and the physiological characteristics of tree peony [13]. And some studies have initially explored the mechanisms underlying the response to heat stress in tree peony [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation